85 The pre-hospital management of acute heart failure: a clinical audit of current practice. (16th April 2018) - Price, J; Murphy-Jones, B; Edwards, T
Abstract : Aim: There has been a drive towards an increase in community-based management of heart failure. When patients experience acute heart failure (AHF), the complex nature of this condition poses diagnostic uncertainty for first responders. It is widely accepted that all patients should be transferred promptly to hospital, however with the introduction of pre-hospital diuresis, nitrate therapy and more recently non-invasive ventilation (NIV), the debate into the appropriateness and limitations of so-called 'stay-and-play' management strategies for patients in AHF has been re-ignited. We examine the current clinical assessment and management of AHF within the London Ambulance Service. Method: Ambulance Patient Report Forms (PRFs) from cases that were coded with heart failure, shortness of breath, cardiac problem and in cases of GTN administration. These cases were further analysed by a clinical review panel to identify patients with suspected AHF. Results: 182 patients were included in the analysis between April and November 2016. There was a 68% compliance with national guidelines for clinical assessment (history, examination and ECG). 51 (28%) patients presenting with AHF were appropriately identified and given a primary diagnosis of AHF by the attending clinician. 136 (76%) patients in the analysis received sublingual nitrate therapy. 90 (49%) patients received nitrates where there was no clinical indication. No patients in the analysis received NIV. Conclusion: Some aspects of AHF assessment and management are not consistent with national guidelines. Our work has further demonstrated the diagnostic challenges facing pre-hospital clinicians and the potential overuse of nitrate therapy in this patient group. Conflict of interest: None Funding: None